EVALUASI KERASIONALAN PENGGUNAAN OBAT DENGAN STANDAR PELAYANAN MEDIS SEBAGAI PENGENDALI PADA PENYAKIT LOW BACK PAIN - Rahmayanti Fitriah (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2019)
Rational use of medicines is one step to get good health services. Rational use of medicines can be identified, one of which begins with rational medicine prescribing. The Indicator that can be used to measure medicine use rationally are by using WHO medicine prescribing indicators (1993) and Medical Service Standards to control medicine use. Low Back Pain is one of the most common diseases in outpatients in Panembahan Senopati General Hospital Bantul. This study used an observational method with a descriptive analytic case study design, using quantitative and qualitative data. The results obtained in Low Back Pain based on WHO prescription indicators (1993) obtained the following results: the average drug items used per prescription sheet were 2.66 items, the percentage of prescription drugs written with generic names was 74.3%, percentage prescription of antibiotics 1.7%, percentage of injection prescription 72.7%, percentage of drug prescription according to hospital formulary 88.2%, percentage of drugs according to DOEN 18.5%, percentage of prescription according to medical service standards 71%, percentage of psychotropic prescribing 12,7%, and the percentage of systemic steroid prescription was 6.3%.